NILAI MORAL DALAM TEKS CERITA RAKYAT MAMASA - Abiatar, Abiatar; Djumingin, Sulastri; AJ, Andi Agussalim (Fakultas Bahasa dan Sastra Indoensia, 2025)
This study aims to describe the moral values contained in Mamasa folk tales. The focus of this study is how moral values are expressed in these folk tales. This study uses a qualitative approach with documentation techniques as the data collection method. The data sources are from the stories ‘Culadidi’, ‘Sarepeo and Saretalana’, ‘Tomase-mase’, and ‘Petani Sawah’ (The Rice Farmer) which are compiled in the book Cerita Rakyat Masyarakat Mamasa (Folktales of the Mamasa People). The main instrument in this study is the researcher himself with the help of data cards to record the findings. The results of the study show that the four Mamasa folk tales contain three main moral values, namely caring, perseverance, and generosity. The value of caring is reflected in empathy and concern for others, which strengthens social harmony. The value of perseverance is evident in the characters' spirit of never giving up in the face of various life challenges. Meanwhile, the value of generosity is evident in the attitude of willingness to share and humility, which reinforces the meaning of gratitude and true happiness. The conclusion of this study is that Mamasa folk tales contain important moral messages in shaping the character and social culture of the community.